Screening of Different Tomato Varieties in Saline Areas of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2013)
A field study was conducted to screen out a number of Bangladeshi Tomato (Lycopersicon esculentum L.) varieties for salinity tolerance. Three levels of salinity were 2.0-4.0 dS m-1, 4.1-8.0 dS m-1 and 8.1-12.0 dS m-1. Significant varietal and or salinity treatment effects were registered on plant height, leaf area, plant growth, yield, dry matter plant-1, Na+ and Claccumulation in tomato tissues. Variety BARI Tomato 14, BARI Hybrid Tomato 5 and BARI Tomato 2 consistently showed superior biological activity at moderate salinity (4.1-8.0 dS m-1), based on dry matter biomass production thus displaying relatively greater adaptation to salinity. Under saline condition, all plant parameters of tomato varieties were reduced compared to the control except number of fruits of BARI Tomato 14, BARI Hybrid Tomato 5 and BARI Tomato 2. Thus, BARI Tomato 14, BARI Hybrid Tomato 5 and BARI Tomato 2 can be regarded as a breeding material for development of new tomato varieties for tolerance to salinity in saline areas of Bangladesh. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13989 Int. J. Agril. Res. Innov. & Tech. 2 (1): 13-18, June, 2012